(untitled) (REMUNOM, 2026)
The Brazilian tax reform introduced by Constitutional Amendment No. 132 of 2023 represents one of the most significant recent transformations in the national tax system, particularly regarding the reorganization of consumption taxation and the incorporation of new constitutional principles guiding fiscal activity. In this context, the present study aims to analyze the constitutional principles introduced by the Brazilian tax reform, considering a humanized approach to taxation and its institutional, economic, and social impacts. To achieve this objective, a qualitative research design was adopted, based on a bibliographic review of recent scientific articles addressing tax reform, constitutional tax principles, and the restructuring of the fiscal system. The results indicate that the reform seeks to simplify the tax structure, reduce distortions arising from tax cascading, and strengthen principles such as simplicity, transparency, and tax neutrality. It is also observed that the reorganization of consumption taxation may contribute to greater legal certainty, administrative efficiency, and improvements in the economic environment. It is concluded that the Brazilian tax reform represents a process of institutional reconfiguration of the fiscal system, in which the incorporation of new constitutional principles points toward the development of a more rational, transparent, and socially oriented tax model.